Associations of serum sLOX-1 levels with disease severity and 3-month function prognosis after spontaneous intracerebral hemorrhage: a prospective cohort study - Ye, Xiufeng; He, Heng; Song, Huan; Huang, Jing; Zhang, Zhixing; Zhou, Yan (Frontiers in Neurology, 2025)
BackgroundSoluble lectin-like oxidized low-density lipoprotein receptor-1 (sLOX-1) may be involved in the inflammatory response and aggravate secondary brain injury after spontaneous intracerebral hemorrhage (sICH). The aim of this study was to reveal the association of serum sLOX-1 levels with disease severity and the predictive power of 90-day neurological outcomes after sICH.MethodThis prospective cohort study included 118 sICH patients and 118 healthy controls, whose serum sLOX-1 levels were quantified. Glasgow Coma Scale (GCS) scores and hematoma volumes were used to assess disease severity. Glasgow Outcome Scale (GOS) scores were used to assess 3-month function prognosis after stroke. The relation of serum sLOX-1 levels to disease severity and prognosis (GOS scores 1–3) was discerned Receiver operating characteristic curve was built to evaluate the prognostic predictive capability.ResultSerum sLOX-1 levels were significantly increased in patients compared to healthy controls, and were independently correlated with GCS scores (ρ = −0.577, p < 0.001; t = −6.732, p < 0.001) and hematoma volumes (ρ = 0.540, p < 0.001; t = 7.136, p < 0.001). Patients with poor prognosis have higher serum sLOX-1 levels than in those with good prognosis (p < 0.001). Serum sLOX-1 levels >1539.75 pg/mL distinguished the risk of poor prognosis at 3 months after stroke, with a sensitivity of 83.72% and a specificity of 72.00% (area under curve, 0.813; 95% confidence interval (CI), 0.731–0.879, p < 0.001). Serum sLOX-1 levels were independently associated with poor 3-month prognosis with odds ratio of 1.002 (95% CI, 1.000–1.004).ConclusionSerum sLOX-1 levels are obviously increased after stroke and are significantly associated with disease severity and poor prognosis. Hence, sLOX-1 may serve as a useful potential prognostic biomarker for sICH.